Needle-Knife Fistulotomy Vs. Standard Biliary Canulation Cannulation: Comparative Study - Abed , Dr. Ibrahim Rahim; Wheeb , Muhannad Ayal; Al-Jubory , Ali Kamil Abd Ali Ali (American Journal of Biology and Natural Sciences, 2025)
Background: the patients with common bile duct (CBD) stones, access to the CBD can be achieved through the papilla orifice followed by standard biliary sphincterotomy (SBS), or through precut fistulotomy (PF) in case of difficult cannulation. The two procedures alter papilla anatomy different ways. Aims: Is to evaluate complication and clearance rate following CBD stone extraction for both ways. Patients and Methods: This was prospective study including 100 patients with common bile duct stone. Patients demographics and clinical characteristics were collected. Indication for ERCP are CBD stones All included patients were subjected to laboratory tests before and after procedure. Patients were divided into two groups 50 patients undergone precut fistulotomy and 50 patients subjected to standard biliary cannulation according to the order of the procedure. The outcomes measured were the number of therapeutic procedures required for complete stone removal and associated complications. Results: Age of patients ranged from (23-68) years, with a mean age of (48.3 ± 12.7) years. The duration of the procedure was significantlyshorter in the standard biliary cannulation (SBC) group (19.2 ± 4.9 min.) compared to the precut fistulotomy (PF) group (32.0 ± 6.6 min.), P-value < 0.001. There were no significant differences in post-ERCPinvestigations or complications between the two groups. However, incases of post-ERCP pancreatitis, the duration of the procedure wassignificantly longer in the PF group compared to the SBC group. P. value= 0.011. Conclusions: The SBC group had shorter procedure durations compared to the PF group. There were no significant differences in stone characteristics or post-ERCP investigations. Complication rates were similar between the groups. Among cases of post-ERCP pancreatitis, the PF procedure had a significantly longer duration.